Leverage Analysis of The Sustainability Index of Plasma Farmers in Teluk Gelam District, Ogan Komering Ilir Regency - Sekar Wahyu Ningsih; Lifianthi Lifianthi; Erni Purbiyanti (Universitas Muhammadiyah Palembang, 2026)
The sustainability of plasma oil palm farming is heavily determined by the farmers' internal resilience against external pressures, particularly those related to financial dependence or financing from partnership credit schemes. Although serving as initial capital, a high ratio of financial obligations has the potential to weaken business resilience and the farmers' long-term sustainability status. This study aims to calculate the multidimensional sustainability index of plasma farmers (economic, environmental, social, technical, and institutional dimensions) and identify the key attributes (leverage) most sensitive to increasing the sustainability index in Teluk Gelam District, Ogan Komering Ilir Regency. The research was conducted using purposive sampling of 50 plasma farmers. Data were collected through structured interviews and literature studies. Sustainability analysis employed the Multi-Dimensional Scaling (MDS) approach via the Rap-PalmOil program. Furthermore, Leverage Analysis from the MDS was used to determine the factors with the highest leverage in enhancing sustainability. The results indicate that the sustainability status of plasma farmers falls into the